The effects of fertilization on the protein related properties of winter wheat - Móré, Mariann; Burján, Zita; Győri, Zoltán; Sipos, Péter (Acta Agraria Debreceniensis, 2013)
The yield and quality of wheat are mainly determined by the plant production system, thus we studied the effect of mineral fertilization. The field trials were set up in 1983 at the Látókép Research Institute of the University of Debrecen. We examined effect of different Nfertilizer doses (60 kg ha-1 N/P/K, 120 kg ha-1 N/P/K) on Lupus, Mv Toldi and GK Csillag’s protein properties in 2012. During the tests, three quality parameters were determined: wet gluten content (%), wet gluten spread (mm/h) and gluten index (%). In the experiment the effect of different doses of N-fertilizers significantly influenced by the wet gluten content and gluten index of Lupus.